Overview of Medication Use in Outpatient Patients at Simpang Tiga Pekanbaru Health Center Based on the World Health Organization's Prescribing Indicators. - Novia Sinata; Hazizah Hazizah (LPPM Universitas Harapan Bangsa, 2023)
The use of drugs prescribed by doctors is very important in providing health services for patient treatment therapy. According to reports received by the World Health Organization (WHO) irrational drug use continues to occur. This is evidenced by more than 50% of drug use being inappropriate when prescribing, while the remaining 50% is caused by inappropriate drug use. This research is a descriptive observational study with retrospective data collection techniques. The sampling method used purposive sampling with the study population all outpatient prescriptions for December 2022 and 320 prescription sheets used as samples according to the inclusion criteria. The results showed that the average number of drug items per prescription sheet was 3.06, the percentage of prescriptions for generic drugs was 98.57%, the percentage of prescriptions for antibiotic drugs was 25%, the percentage of prescriptions for injection preparations was 0%, and the percentage of prescriptions according to the National Formulary was 89.49%. It is hoped that this research can be used as an illustration and information in controlling rational drug use.